Student Assistance in Social Activities to Increase Creativity and Independence through Free Food Program - Supriadi; Rahmawati, Sri; Bayu Putra, Rizky Perdana; Ainur Rahim Setiawan; M. Zainul Muttaqin; Sarlotha Selan; Liza Choirun Nisa' (⁠International Journal of Asia Pacific Community Service, 2024)
This community service program aims to enhance the creativity and independence of students through social activities such as the distribution of free food to the community around the campus. Student involvement in this program is designed to provide practical experience in planning, organizing, and implementing social activities that have a positive impact. Students involved in this program not only learn about the importance of empathy and social responsibility but also develop managerial, communication, and creativity skills. Through a participatory approach, students are encouraged to identify community needs, design innovative solutions, and implement them independently. The results of this program show that students actively participating in these social activities experience significant improvements in creativity and independence. Additionally, this program successfully strengthens the relationship between students and the surrounding community, creating a beneficial synergy for both parties. These findings emphasize the importance of integrating social activities into higher education curricula as an effort to equip students with relevant skills to face future challenges. Thus, this mentoring program not only provides direct benefits to the community receiving assistance but also shapes students' character and capabilities more comprehensively.